2000
DOI: 10.1164/ajrccm.162.1.9911019
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Viral Infections in Adults With and Without Chronic Obstructive Pulmonary Disease

Abstract: A longitudinal cohort study of older adults with chronic obstructive pulmonary disease (COPD) who were stratified by FEV(1) at enrollment was done to define the etiology, frequency, severity, and medical-care impact of respiratory tract viral infections (RTVIs). Controls consisted of a group of subjects of comparable age with the patients. RTVIs were documented in 44% of observed acute respiratory illnesses in control subjects and in 27% of COPD subjects, who were followed for mean periods of 35 and 26 mo, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
192
2
11

Year Published

2002
2002
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 224 publications
(214 citation statements)
references
References 27 publications
9
192
2
11
Order By: Relevance
“…The definition of lower respiratory tract involvement in the latter studies was less stringent than that defining exacerbation in the present report. Therefore, it is suggested, in agreement with GREENBERG et al [13], that COPD patients as a group are not more susceptible to respiratory viral infections, and, in agreement with NICHOLSON and coworkers [16,17], that patients with COPD do not appear more likely to develop lower respiratory tract symptoms during such events than other elderly subjects. However, the current authors have shown that cold frequency in COPD is variable, and this masks an important effect in frequent exacerbators who do indeed have an increased frequency of colds.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The definition of lower respiratory tract involvement in the latter studies was less stringent than that defining exacerbation in the present report. Therefore, it is suggested, in agreement with GREENBERG et al [13], that COPD patients as a group are not more susceptible to respiratory viral infections, and, in agreement with NICHOLSON and coworkers [16,17], that patients with COPD do not appear more likely to develop lower respiratory tract symptoms during such events than other elderly subjects. However, the current authors have shown that cold frequency in COPD is variable, and this masks an important effect in frequent exacerbators who do indeed have an increased frequency of colds.…”
Section: Discussionsupporting
confidence: 77%
“…Indeed, given the conflicting results of previous studies comparing the incidence of respiratory viral infections in patients with COPD versus control subjects, there is a need for further data in this area. The most recent work, by GREENBERG et al [13], suggested that whilst patients with COPD experience more total episodes of respiratory illness than age-matched control subjects (largely exacerbations of COPD), there was no excess incidence of respiratory viral infections. This contradicted a number of older studies, including that by MONTO et al [14], who reported that patients with chronic bronchitis did have a higher incidence of serologically proven rhinoviral infections.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, influenza A virus increased permeability of polarized airway epithelial cells by inducing cytotoxic effects, whereas RSV had no effect on either R T or ZO-1 distribution. These studies provide insight into a new mechanism by which RV may predispose the host to secondary bacterial infection, as occurs in otitis media (1,12) and exacerbations of COPD (4)(5)(6)(7).…”
Section: Discussionmentioning
confidence: 98%
“…RVs are single-stranded RNA viruses responsible for the majority of upper respiratory tract infections and their complications, including otitis media, sinusitis, and bronchitis. By a sensitive detection method (polymerase chain reaction), RV was detected in 25.6% of viral-induced acute otitis media (1), and up to one-half of all viral-associated COPD and CF exacerbations (4)(5)(6)(7)9). In each of these conditions, coinfection of RV and bacteria are thought to play an important pathogenetic role.…”
mentioning
confidence: 99%
“…COPD patients often experience exacerbations, which are an acute worsening of symptoms beyond the normal dayto-day variation [1]. Exacerbations of COPD, which are associated with a worse quality of life [2] and increased mortality [3], are more frequent during the winter season [4,5], being associated with an increased prevalence of infections with respiratory viruses [6]. These winter exacerbations have a greater impact on patients in terms of hospitalisations and recovery [5].…”
mentioning
confidence: 99%